Research on Dunhuang cultural and creative product design / Liu Qing, Amer Shakir Zainol and Nurul Huda Mohd Din - Qing, Liu; Zainol, Amer Shakir; Mohd Din, Nurul Huda (College of Creative Arts, 2024)
In the context of the development of cultural and creative industries, the preservation and transmission of cultural heritage are facing many new opportunities. Using creative design to transform cultural heritage content into cultural and creative products and build a pathway between cultural heritage and contemporary life is a good way to perpetuate cultural heritage. This study reviews the literature on Dunhuang culture and creative products, surveys Dunhuang creative products, collates the current state of Dunhuang cultural creativity, analyses basic design methods for the application of Dunhuang culture to creative design, and makes recommendations for future Dunhuang creative research and development. This study demonstrates the achievements of Dunhuang's cultural creation and contributes to the sustainability of Dunhuang's cultural heritage.